Hukum Islam dan Hak Asasi Manusia - Rejal Miftahul Fajar (Justicia Islamica, 2008)
This study aims to examine the relationship between Islamic law and human rights (HAM), as well as how sharia principles can contribute to the protection and promotion of human rights in modern society. This study uses a qualitative method with a literature study approach, examining the main sources of Islamic law such as the Qur'an, Hadith, and international documents on human rights. The results of the study show that Islamic law basically supports human rights values, such as the right to life, freedom of religion, justice, and equality before the law. However, there are challenges in the interpretation and implementation of these norms in several social and political contexts. This study emphasizes the importance of the maqashid sharia approach and the contextualization of Islamic law so that the universal values of human rights can be in harmony with the principles of sharia in a substantive and applicative manner.